APLIKASI KEAMANAN SMS MENGGUNAKAN ALGORITMA TRIPLE-DES DAN PENGUJIAN SERANGAN MAN IN THE MIDDLE ATTACK (MITM) DENGAN METODE SNIFFING - Sri Wayun Wardani; Sutardi Sutardi; Statiswaty Statiswaty (semanTIK, 2019)
An increasing number of mobile phone users and the number of Short Message Service (SMS) delivery between users, securities SMS sending an issue that deserves to be noticed. SMS industry into one vulnerable point to attack a security threat. The security hole on SMS communication is a message sent will be stored in the Short Message Service Center (SMSC), so that in case of attack Man In The Middle (MITM) at the SMSC then sent messages to be read by those who tapped one of them is sniffing activity. So, we need a safeguard against the activity of the exchange of messages via SMS. One of them is by using cryptography. Cryptography is a technique to secure the message so that the message conveyed to arrive to the person intended, receives the message. Cryptography is composed of two main concepts that encryption and decryption. Encryption is used to process information becomes unrecognized and decryption is used to change the information that was not recognized into information that is recognizable as before encryption. By encrypting text, the level of information security of the message can be improved. Currently, the Triple-DES (Triple Data Encryption Standard) is a secure cryptography algorithm for encryption process is carried out in 3 stages but did not change the algorithms of DES in order to ensure the complexity of solving the results of Triple-DES encryption. Therefore, it can be prepared that, if the intruder was given a person or an attack using a sniffing methods, the received message by the perpetrators are not illegible.Keywords—Cryptography, Man In The Middle Attack, Sniffing, SMS, Triple-DES DOI : 10.5281/zenodo.3227231